Inhibitory Control Development: A Network Neuroscience Perspective - Kang, Weixi; Hernández, Sònia Pineda; Rahman, Md. Shahinoor; Voigt, Katharina; Malvaso, Antonio (Frontiers in Psychology, 2022)
As one of the core executive functions, inhibition plays an important role in human life through development. Inhibitory control is defined as the ability to suppress irrelevant thoughts and information from the external environment but focus on whatever is relevant to our goals. Contemporary neuroscience has investigated the underlying neural mechanisms of inhibitory control. Controversy starts to arise which resulted in two schools of thought: a modulatory and a globalist account of inhibitory control. More recently, growing interest tries to understand developmental mechanisms in inhibitory control using a variety of functional imaging methods. In this review, we survey developmental mechanisms in inhibitory control and argue against the modulatory perspective of inhibitory control: the improvement in inhibitory control does not depend on a dedicated region such as the rIFG, but rely on the developments of a more broadly distributed system.